THE RELATIONSHIP OF TECHNICAL SCIENCES WITH PHYSICS IN PREPARING STUDENTS FOR TECHNICAL CREATIVE ACTIVITY - Alkarov Kadir Kholmatovich (Web of Journals Publishing, 2025)
In this article, there are opinions about the relationship between physics and technical sciences and their training in preparing students for technical creativity.
Keywords: Robust, search, creativity, scientific and technical, measurement, management, hardware synchronization.